Penelitian standard ukuran sepatu anak-anak indonesia - Suliestiyah Wiryodiningrat; Dwi Asdono Basuki (Majalah Kulit, Karet, dan Plastik, 1994)
This research is aimed at compilation of size standard of Indonesian children shoes, for it is abviously that the available size systems currently, such as English system, American system and French system are not suitable with Indonesian foot sizes. Samples of the research were taken from children foot sizes of DIY using area purposive sampling, while data analvsis method used was Statistical of M (Mean) and SD (Standard of Deviation). The foot size data were calculated using comparison parameter of breadth to length size, joint girth, instep girth and short heel. Result of the research showed that the increase of each size number was 6,75 mm; breadth figure and joint, girth size got a raise in, successivelv of 2,75 mm and 6,25 mm in harmonv for each size number, which were classififield into narrow. medium and wide fitting.